Determinants of Zakat Management Policy Implementation in Enrekang Regency - Busa, Yunus; Witteveen, Loes; Elihami, Elihami; Nurdin, Nurdin; Masnur, Masnur; Anugrah, Dian (Journal of Local Government Issues, 2025)
This study examines the determinant factors influencing implementing zakat management policies in Enrekang Regency. Employing a descriptive qualitative method, the research adopts an explanatory phenomenological approach to explore and interpret zakat management's causal and chronological dimensions. Data were collected through interviews, field observations, and documentation analysis using instruments such as interview guides, observation sheets, and document review protocols. The NVivo 12 Plus software assisted in data organization and interpretation. This findings indicate that several key factors significantly affect zakat policy implementation: government support, public awareness and trust in zakat institutions, the professionalism of zakat managers (amil), community religiosity, understanding of zakat regulations, inclusive socialization efforts in rural areas, comprehensive zakat implementation mechanisms, adaptability of information systems, local culture of sharing, and transparency of the UPZ (zakat collecting unit). These elements interact to shape the effectiveness of zakat governance, particularly in the digital era, where zakat institutions are increasingly required to integrate digital-based systems and respond to evolving information needs. The research highlights the necessity for BAZNAS and related stakeholders to enhance digital literacy, technological adaptation, and community engagement to improve zakat services.